Tinjauan Awal Kes-Kes Integriti dan Rasuah melibatkan Ahli Politik Malaysia - Khadijah Muda; Ros Aiza Mohd Mokhtar; Kamal Azmi Abd Rahman; Siti Nor Baya Mat Yacob; Siti Nor Azhani Mohd Tohar (Penerbit UKM, 2025)
Indexed